Pékin entre patrimoine et modernité : une mutation de la morphologie urbaine observée par satellite depuis 50 ans - Antoine Lefebvre (Cybergeo, 2017)
Urban areas in China have dramatically changed since its opening to a market economy in 1978. In Beijing, the transformation of the old city reflects modifications in society, politics and economy. The old urban pattern, that has a unique architectural and social heritage, has been demolished at the expense of business centers, shopping malls and luxury housing. This article proposes to monitor these changes using satellite images. The results allow us to date, quantify and spatialize morphological changes. Results are compared with bibliographic references and highlight urban development policies such as housing reform in 1991 and preparation for the 2008 Olympic Games. It is estimated that over half of the old urban pattern was demolished, and it is showed that Chinese authorities have difficulties to preserve its heritage while meeting the needs of urban modernity.